Incorporating Individual Patient Preferences in Scheduling Bitewing Radiographs - Pliskin, J. S.; Shwartz, M.; Gröndahl, H. G.; Boffa, J. (Methods of Information in Medicine, 1985)
Concern about the potential risks of low dose radiation has focussed increased attention on the question of how often to perform bitewing radiographs. To consider this question, a mathematical model was developed that describes the initiation and progression of dental caries on the approximal surfaces of permanent teeth. This model enables calculation of benefit as a function of the frequency of bitewing radiographs. The model does not, however, capture patients’ (and dentists’) subjective attitudes towards various outcomes such as dollar costs, radiation exposure, inconvenience of treatment, anxiety and pain. This paper presents a multiattribute utility approach to quantifying patient preferences for possible outcomes of decisions on radiographic frequencies. Five relevant attributes are considered and reduced to two, over which a quasi-additive utility function is found plausible. The paper demonstrates the assessment method and presents aggregate data from a group of individuals.
Keywords: Multiattribute Utility Assessment; Radiographs; Dental Caries